A case of double cystic esophageal duplication in VACTERL syndrome: the first case report and a review of the literature - G. Vasta; G. Vasta; S. Tursini; E. Rovero; R. Angotti; F. Molinaro; V. Briganti (Frontiers in Pediatrics, 2023)
BackgroundAn esophageal duplication cyst (EDC) is a rare malformation resulting from the embryonic foregut. VACTERL syndrome is a genetic disorder affecting many systems of the human body. We report the first case of VACTERL syndrome associated to asymptomatic double EDC.Case reportA girl with anorectal malformation and rectovestibular fistula, kidney malformation, and various vertebral defects came to our attention at the time of birth. VACTERL disease was diagnosed. She underwent Peña anoplasty at 4 months of life without complications. MRI was conducted at the age of 2. It accidentally showed a double esophageal duplication (12 mm × 35 mm × 10 mm) at the D7–D9 level. We planned a thoracoscopy; previous intraoperative esophagogastroduodenoscopy showed an external compression of the native esophagus. Two duplicated esophageal lesions were removed. The patient made an uneventful recovery and was completely asymptomatic at long-term follow-up.ConclusionsVACTERL syndrome is still a not well-defined disease. Based on the current literature, this is the first case of a double esophageal duplication in a patient affected by VACTERL syndrome. According to us, the thoracoscopic approach of esophageal duplications can be followed by experts. Complete surgical excision is possible even if the cyst shares a common muscular wall with the esophagus. For this reason, we suggest to close the muscular wall by a simple interrupted suture.